IL-10/TGF-β–Modified Macrophages Induce Regulatory T Cells and Protect against Adriamycin Nephrosis - Cao, Qi; Wang, Yiping; Zheng, Dong; Sun, Yan; Wang, Ya; Lee, Vincent W.S.; Zheng, Guoping; Tan, Thian Kui; Ince, Jon; Alexander, Stephen I.; Harris, David C.H. (Journal of the American Society of Nephrology, 2010)
IL-10/TGF-beta-modified macrophages, a subset of activated macrophages, produce anti-inflammatory cytokines, suggesting that they may protect against inflammation-mediated injury. Here, macrophages modified ex vivo by IL-10/TGF-beta (IL-10/TGF-beta Mu2) significantly attenuated renal inflammation, structural injury, and functional decline in murine adriamycin nephrosis (AN). These cells deactivated effector macrophages and inhibited CD4+ T cell proliferation. IL-10/TGF-beta Mu2 expressed high levels of the regulatory co-stimulatory molecule B7-H4, induced regulatory T cells from CD4+CD25- T cells in vitro, and increased the number of regulatory T cells in lymph nodes draining the kidneys in AN. The phenotype of IL-10/TGF-beta Mu2 did not switch to that of effector macrophages in the inflamed kidney, and these cells did not promote fibrosis. Taken together, these data demonstrate that IL-10/TGF-beta-modified macrophages effectively protect against renal injury in AN and may become part of a therapeutic strategy for chronic inflammatory disease.